Spatial distribution of innovation activities in Czech Republic, 2010-2012 - Marek Vaculík; Vít Pászto; Barbora Švarcová (Journal of International Studies)
Innovation is widely considered as an engine of economic growth, competitiveness and job creation. As such it has become a hot policy topic over the last years, especially on regional and national levels. Thus, it is vital to analyze and evaluate innovation activities, whether they are dispersed or concentrated in space. This article address the question: are innovations spatially clustered or not? In this article, we obtain a clear picture of the geographical distribution of innovation activities carried out by companies in Czech Republic during 2010-2012. Visual and statistical analysis of firm-level survey data concerning innovation activities of 5,449 (22% of the statistical population) Czech companies has been performed. Using four newly calculated innovation measures, their overall scores in Local Administrative Units 1 and consequent geovisualization allowed us revealing clusters of innovating districts and evaluating their spatial patterns. The main findings are that low innovative regions are located mainly (1) in the borderlands, (2) in rural areas, and (3) in mountainous areas. On the other hand, highly innovative regions tend to be in major cities and their neighborhoods, which indicates a positive spillover effect.